Network Pharmacology-Based Prediction and Verification of Ginsenoside Rh2-Induced Apoptosis of A549 Cells via the PI3K/Akt Pathway - Song, Chao; Yuan, Yue; Zhou, Jing; He, Ziliang; Hu, Yeye; Xie, Yuan; Liu, Nan; Wu, Lei; Zhang, Ji (Frontiers in Pharmacology, 2022)
Ginsenoside Rh2, a rare protopanaxadiol (PPD)-type triterpene saponin, from Panax ginseng has anti-proliferation, anti-invasion, and anti-metastatic activity However, the mechanisms by which ginsenoside Rh2 induces apoptosis of lung cancer cells are unclear. A ginsenoside Rh2 target-lung cancer network was constructed and analyzed by the network pharmacology approach, identifying the PI3K-Akt signaling pathway. Ginsenoside Rh2 significantly inhibited proliferation and induced apoptosis and cell cycle arrest in A549 cells. Ginsenoside Rh2 inhibited the PI3K-Akt signaling pathway, consistent with the network pharmacology results. These findings will provide the potential therapeutic value for further mechanism investigations.